The Relationship between unsystematic risk and returns at the Nairobi Securities Exchange - Omeri, Daniel Nyangwono (Strathmore University, 2021)
This study sought to assess the relationship between unsystematic risk and returns in the Kenyan stock market by looking at firms that are listed at the Nairobi Securities exchange. Unsystematic risk is a factor that investors consider when making investment choices. Whereas institutional investors diversity to minimize this risk, retail investors are exposed to unsystematic risk since they hold single stocks. This fanned the basis of this study as it sought further to explain the role that unsystematic risk plays in the determination of stock rettm1s at the Nairobi Securities Exchange. The period of study \vas between 2010 and20 19 with the objectives of examining the trend of unsystematic 1isk, investigating the forecasting ability of unsystematic risk on stock returns, and determine the optimum portfolio for an investor at the Nairobi Securities exchange. Portfolios were formed using a purposive sampling method as securities were organized in ascending order of their unsystematic risk values and portfolios selected in the increasing order of the unsystematic risk values. To calculate unsystematic 1isk, CAPM was used to control for firm-specific risk, which was determined as the standard deviation of the residuals from regressing excess rettm1s. This study adopted a positivism research philosophy and a quantitative research design. Secondary data was used in the study and was collected using a data capture sheet. The study used trend analysis, regression analysis, and a mean-variance model to analyze data. Three diagnostic tests, tests for normality, stationarity, and autocorrelation were conducted to ensure that the findings don't lead to a spurious regression. From the result of the trend analysis, value-weighted unsystematic risk showed an insignificant trend for the period of study. The study revealed that unsystematic risk is negatively related to the stock market rectums and cannot forecast stock market returns at NSE. Furthermore, an investor needed a portfolio of between 17 to 22 securities to achieve an optimum p01tfolio at Nairobi Securities Exchange. This study contributes to the existing knowledge of the relationship between unsystematic risk and stock market returns in developing and emerging capital markets.
A Research thesis submitted in partial fulfillment of the requirement for the Degree of Master of Commerce at Strathmore University